The Thames and Hudson Dictionary of Graphic Design and Designers / 445 Illustrations, 59 in Colour - Livingston Alan.; Livingston Isabella; Thames And Hudson (1996)
A comprehensive guide to the international developments in Graphic Design. A Reader's Guide to the Use of this Book, Subject Index, The Dictionary, Chronological Chart, Bibliography, Sources of Illustrations.